Solitary dural metastasis at presentation in a patient with untreated human papillomavirus–associated squamous cell carcinoma of the oropharynx. Issue 10 (20th March 2014) - Al‐Khudari, Samer; Guo, Susan; Chen, Yunwei; Nwizu, Tobenna; Greskovich, John F.; Lorenz, Robert; Burkey, Brian B.; Adelstein, David J.; Koyfman, Shlomo A.; Chen, Amy
Abstract Background Human papillomavirus (HPV)‐associated oropharyngeal squamous cell carcinoma (SCC) is associated with high cure rates and distant metastases are rare. Methods and Results We report a case of a 61‐year‐old man presenting with acute left‐sided weakness. An enhancing dural mass was noted and resected. Histology revealed p16‐positive SCC. Further workup revealed a p16‐positive right tonsillar primary with ipsilateral nodal disease and was classified as T2N2bM1. The patient underwent whole brain irradiation and definitive chemoradiation with curative intent. Complete clinical response was achieved and the patient continues to be disease‐free 6 months posttreatment. Conclusion HPV‐associated oligometastatic oropharyngeal SCC is a rare entity that may have a unique natural history and behavior. Given the excellent treatment response and prognosis of HPV‐positive disease in general, these patients may be appropriate for definitive treatment approaches. © 2014 Wiley Periodicals, Inc. Head Neck, 36: E103–E105, 2014